Peran Sosialisasi dan Edukasi Kewirausahaan dalam Membangun Generasi Milenial Berjiwa Wirausaha: Studi Kasus di Kelurahan Perdagangan I - Agung Satya Nugraha; Arif Winanda Panggabean; Dandi Wahyuda; Salman Nasution (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to analyze the role of entrepreneurship socialization and education in fostering the entrepreneurial spirit among the millennial generation, with a case study focus in Kelurahan Perdagangan I, Simalungun Regency. Entrepreneurship socialization and education are crucial steps in fostering entrepreneurial awareness and skills, especially for the younger generation who will face economic challenges in the future. This research used a qualitative method with a case study approach. Data were collected through in-depth interviews with program participants, direct observation in the field, and document analysis related to the KKN program in Kelurahan Perdagangan I. The results showed that the program was successful. The results showed that the entrepreneurship socialization and education program implemented through KKN succeeded in increasing participants' entrepreneurial knowledge, interest, and skills. In particular, SMK students showed increased motivation to start a business after participating in entrepreneurship education. The success of the program was supported by active community involvement and a contextually relevant approach. However, there are some challenges, such as limited access to technology and financial resources, that affect the sustainability of entrepreneurial interest among the millennial generation.